Can proprioception be improved by exericse? - Li, J. X. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The study examined if regular exercise with high demand in postural control and cyclic exercise could improve proprioception of the foot and ankle complex. A total of 38 young health people with different exercise habits for more than five years formed three groups: the ice hockey, running, and sedentary groups. Kinesthesia of the foot and ankle complex was measured in plantarflexion (PF), dorsiflexion (DF), inversion (IV) and eversion (EV) at 0.4°/s passive rotation velocity using a custom-made device. The results showed that the hockey group had significantly better kinesthesia in PF/DF, IV/EV than did the running and sedentary groups. The running group did not show better kinesthesia compared with the sedentary group. It is concluded that propiorception of foot and ankle complex can be improved by longterm exercise that has high demand for postural stability, such as ice hockey.